Developing an innovation and enterprise framework for translating UK-driven global health research into commercially viable interventions: the FLIGHT study protocol. - Ezekiel Boro; Charles McLoughlin; Tom Vaughan; Carolina Velasco; Lisa Tilokani; Katherine Prescott; Gail Davey; Simon J Waddell; Alexandra Anderson; Justin Pulford; Chris Peters; Becky Jones-Phillips (PLoS ONE)
The UK Higher Education Institution (HEI) sector faces significant challenges in translating early-stage research into commercially viable public health products, particularly in infectious diseases. This gap, often termed the "valley of death," is exacerbated by a fragmented ecosystem and unclear pathways to implementation. The FLIGHT (Framework for Leveraging Innovation in Global Health Technologies) project aims to address these challenges by enhancing the commercialisation of global health research from UK HEIs to drive economic and societal impact. Led by Liverpool School of Tropical Medicine, in partnership with London School of Hygiene and Tropical Medicine, Brighton and Sussex Medical School, and other associated partners, FLIGHT seeks to develop a best practice Innovation and Enterprise Framework (IEF) to support R&D commercialisation. This project will use a mixed-methods approach to assess existing public health R&D assets and the commercialisation knowledge and skills of HEI professionals and Early Career Researchers (ECRs) across partner institutions. Data collection will include literature reviews, surveys, qualitative interviews, and focus group discussions exploring staff and ECR's perceptions and experiences with commercialisation, to identify barriers and opportunities for improvement. Ethical considerations and participant confidentiality are central to the study design. The FLIGHT project aims to bridge critical gaps in the innovation pipeline, fostering a robust ecosystem for translating HEI research into deployable health interventions. This initiative will contribute to strengthening the UK's global health R&D commercialisation capabilities and accelerating the development and deployment of essential public health interventions. Findings will inform policy recommendations and best practice for HEI commercialisation strategies, with implications for both UK and low-and middle-income country (LMIC) contexts.